Some aspects of spiritual thoughts of Shaykh ‘Abd Al-Ṣamad Al-Falimbānī (D. 1243/1828) / Nik Roskiman Bin Abdul Samad - Nik Roskiman, Abdul Samad (2013)
It is commonly believed that in the early phase of Islamization of the Malay Archipelago, Islam was presented to the indigenous people in the form of syncretistic Sufism. The version of Sufism that had been widely propagated then was the wujūdiyyah doctrine identical to the waḥdat al-wujūd attributed to Ibn ‘Arabī (d. 637/1240). Early Malay scholars like Hamzah al-Fansūrī (d.1015/1607) and Shams al-Dīn al-Sumatrānī (d. 1039/1630) were among the forerunners of this doctrine. This group was vehemently opposed by Orthodox Sunni scholars represented by people like Nūr al-Dīn al-Ranīrī (d.1068/1658) and moderately by ‘Abd al-Ra‘ūf al-Sinkilī (d. 1104/1693). Around the eighteenth century of the Christian Era, there rose a group of scholars who tried to reconcile the two conflicting groups. One of them was ‘Abd al-Samad al-Falimbānī (d.1202/1788). Together with him were people like Muh}ammad Nafīs ibn Idrīs al-Banjārī (d.1147/1735) and Dawūd al-Fatānī (d.1263/1847). They tried to harmonise the wujūdiyyah approach with that of orthodox mainstream Sunnī Islam. In their attempt to resolve the differences of the two opposing trends, al-Falimbānī brought to the Malay world for the first time the teachings of a moderate and sober Ṣūfī scholar, Hujjat al-Islam Abū Ḥamid al-Ghazālī (d. 505/1111). For many centuries, al-Falimbānī has left great impact on the development of Islam and the Muslims in the Archipelago and it is still felt until this present days. This research analyses the spiritual and metaphysical thought al-Falimbānī which is imbued with al-Ghazālī’s methodology and worldview. It discusses, among other things, the biographical details of al-Falimbānī and tries to ascertain the most reliable position on some matters whenever possible; the impact of al-Falimbānī’s predecessors have had on the Muslims and Islam in the Archipelago that al-Falimbānī eventually inherited; his mystical teachings and finally this work attempts to answer several major criticisms raised by the modern reformers and critics of al-Falimbānī’s mystical teachings.